Pengembangan Video Animasi Toonly Pada Mata Kuliah Bunpo Shochukyu Bab 41-43 - Ni Kadek Intan Permata Sari; Yeni Yeni; Kadek Eva Krishna Adnyani (Universitas Negeri Padang, 2023)
This study aims to develop an appropriate animated video form for the Bunpo Shochukyu course chapters 41-43 at the Japanese Language Education Study Program UNDIKSHA and analyze the feasibility level of the animated video being developed. The model used is the Multimedia Development Life Cycle (MDLC) which was introduced by Luther Sutopo and modified by Binanto (2010). The development of this learning video was carried out based on the results of semi-structured interviews by supporting lecturer 1 and supporting lecturer 2 to find out the obstacles to the Bunpo Shochukyu course in the UNDIKSHA Japanese Language Education Study Program. The distribution of questionnaires to students was also carried out to determine the readiness, strengths and weaknesses of the learning media used and the distribution of a second questionnaire to determine the characteristics of the desired learning media. The results of this study are 3 animation-based shochukyu bunpo learning videos which are equipped with backsound and have passed the feasibility test stage by alpha test and beta test. The first assessment by media experts obtained an average of 57 and the assessment by material experts obtained an average of 53. The second assessment by media experts obtained an average of 59 and the assessment by material obtained an average of 52. The beta test was carried out by 6 students and obtained an average of 98.5. The results of the assessment on the alpha test and beta test stated that the learning video developed was feasible to use.